Contributions to Ergodic Theory and Probability: Proceedings of the First Midwestern Conference on Ergodic Theory held at the Ohio State University, March 27–30, 1970 - Sucheston, Louis (Lecture notes in mathematics, 1970)
Continuous flows in the plane -- New conditions for existence of invariant measures in ergodic theory -- Approximation and spectral multiplicity -- Approximation and invariance -- On some applications of probability methods to additive number theoretic problems -- Example of an ergodic measure preserving transformation on an infinite measure space -- Some results on convergence rates for weighted averages -- A note on ?-finite invariant measures -- Super-mean-valued functions and semipolar sets -- Liftings and derivation bases -- Lipschitz functions and the prevalence of strict ergodicity for continuous-time flows -- Weak ratio convergence of measures in infinite measure spaces -- Transformations without finite invariant measure have finite strong generators -- On the Araki-Woods asymptotic ratio set and non-singular transformations of a measure space -- Imbedding Bernoulli shifts in flows -- On the existence of a ?-finite invariant measure under a generalized Harris condition -- The Ambrose-Kakutani theorem and the poisson process -- Generalized martingales -- Local ergodic theorems for N-parameter semigroups of operators.